2005
DOI: 10.1080/00016480510026269
|View full text |Cite
|
Sign up to set email alerts
|

Latin American experience with the cochlear implant

Abstract: 26 cases (0.7%), with no significant relationship to device type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In a study carried out in Latin America involving 40 cochlear implant centers in 10 countries, with a sample of 3,768 implanted patients, there were 193 postoperative complications (5.1%), and the major causes were: spontaneous system failure (86 cases), skin inflammation caused by the magnet (35 cases) and infection (26 cases). In this study, the author concluded that such complications are commonly associated to the type of cochlear implant 6 . American Cochlear Implant Centers reported an incidence of major and minor complications of 8% and 4.3%, respectively, in a sample of 2,751 implanted patients 3 .…”
Section: Introductionmentioning
confidence: 98%
“…In a study carried out in Latin America involving 40 cochlear implant centers in 10 countries, with a sample of 3,768 implanted patients, there were 193 postoperative complications (5.1%), and the major causes were: spontaneous system failure (86 cases), skin inflammation caused by the magnet (35 cases) and infection (26 cases). In this study, the author concluded that such complications are commonly associated to the type of cochlear implant 6 . American Cochlear Implant Centers reported an incidence of major and minor complications of 8% and 4.3%, respectively, in a sample of 2,751 implanted patients 3 .…”
Section: Introductionmentioning
confidence: 98%
“…The use of cochlear implant (CI) in children provides important benefits for the development of listening and communication skills and allows their progress in school and, later on, in the ability to obtain, maintain, and perform a professional occupation. As a result, many children in the world have been receiving the CI (1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies report a low overall rate (about 1%) of electrode migration 15 , but some authors have found that it is a leading cause of reimplantation, second only to device failure 20 , 23 . A review of 3,773 cases in Latin America 24 showed that full migration occurred in 13 cases (0.35%), most of them associated with ceramic implants (ClarionT, MED-ELT, 3MT).…”
Section: Discussionmentioning
confidence: 99%